CORRELATIONS OF DIFFERENT STRUCTURAL AND FUNCTIONAL CHARACTERISTICS OF ARTERIAL WALL WITH TRADITIONAL CARDIOVASCULAR RISK FACTORS IN HEALTHY PEOPLE OF DIFFERENT AGE. PART 1 - I. D. Strazhesko; O. N. Tkacheva; D. U. Akasheva; E. V. Dudinskaya; M. V. Agaltsov; A. S. Kruglikova; N. V. Brailova; V. S. Pykhtina; E. V. Plokhova; N. V. Sharashkina; O. Yu. Isaykina; V. A. Vygodin; et al. (Столичная издательская компания, 2016)
Arterial wall status is determined by several characteristics, the main of them are as follows: pulse wave velocity (PWV), carotid arteries intima-media thickness (IMT), the presence of atherosclerotic plaques, endothelium-dependent vasodilation (EDVD). When these parameters change, the risk for cardiovascular disease (CVD) grows. The nature of relationship between these indices in people without CVD clinical signs is understudied, especially in those of older age.Aim. To estimate correlations between different parameters of arterial wall in patients of different age without CVD.Material and methods. A total of 303 people aged 25-91 years without any manifestations of CVD or other chronic diseases and without regular medical treatment were examined. PWV estimation, carotid ultrasound with IMT measurement and atherosclerotic plaques amount calculation and EDVD estimation using reactive hyperemia test were performed. Results. Patients without CVD clinical signs rather often reveal arterial wall lesions already in the younger age group (mean age 40.9±8.7): reduced EDVD - in 26% of the cases, the presence of atherosclerotic plaques - in 22%, increased PWV - in 15%, increased IMT - in 8%. The prevalence of arterial wall alterations in the older age group (mean age 61.19±8.5) increase many-fold. All arterial wall parameters correlate with age. The stronger correlation was revealed between IMT and the amount of atherosclerotic plaques: r=0.46 (р<0.001) in the younger group and r=0.47 (р<0.001) in the older one. We didn't find any relationship between PWV and EDVD in the younger group and between PWV and the amount of atherosclerotic plaques in the older one. Thickened carotid intima-media increases the risk of arterial stiffness by 2.3 times.Conclusion. Estimation of the state of arterial wall in people of young age without CVD allows detecting individuals who require active CVD prevention. Increased stiffness of arterial wall and the development of subclinical atherosclerosis represent different phenotypes of alterations.